Independent predictors for 90-day readmission of emergency department patients admitted with sepsis: a prospective cohort study - Stenholt, Peer Oscar Overgaard; Abdullah, S. M. Osama Bin; Sørensen, Rune Husås; Nielsen, Finn Erland (BMC infectious diseases, 2021)
The primary objective of our study was to examine predictors for readmission in a prospective cohort of sepsis patients admitted to an emergency department (ED) and identified by the new Sepsis-3 criteria. A single-center observational population-based cohort study among all adult (≥18 years) patients with sepsis admitted to the emergency department of Slagelse Hospital during 1.10.2017-31.03.2018. Sepsis was defined as an increase in the sequential organ failure assessment (SOFA) score of ≥2. The primary outcome was 90-day readmission. We followed patients from the date of discharge from the index admission until the end of the follow-up period or until the time of readmission to hospital, emigration or death, whichever came first. We used competing-risks regression to estimate adjusted subhazard ratios (aSHRs) with 95% confidence intervals (CI) for covariates in the regression models. A total of 2110 patients were admitted with infections, whereas 714 (33.8%) suffered sepsis. A total of 52 patients had died during admission and were excluded leaving 662 patients (44.1% female) with a median age of 74.8 (interquartile range: 66.0-84.2) years for further analysis. A total of 237 (35,8%; 95% CI 32.1-39.6) patients were readmitted within 90 days, and 54(8.2%) had died after discharge without being readmitted. We found that a history of malignant disease (aSHR 1,61; 1.16-2.23), if previously admitted with sepsis within 1 year before the index admission (aSHR; 1.41; 1.08-1.84), and treatment with diuretics (aSHR 1.51; 1.17-1.94) were independent predictors for readmission. aSHR (1.49, 1.13-1.96) for diuretic treatment was almost unchanged after exclusion of patients with heart failure, while aSHR (1.47, 0.96-2.25) for malignant disease was slightly attenuated after exclusion of patients with metastatic tumors. More than one third of patients admitted with sepsis, and discharged alive, were readmitted within 90 days. A history of malignant disease, if previously admitted with sepsis, and diuretic treatment were independent predictors for 90-day readmission.